2016
DOI: 10.1002/ijc.30443
|View full text |Cite
|
Sign up to set email alerts
|

Use of benzodiazepine and risk of cancer: A meta-analysis of observational studies

Abstract: Several observational epidemiological studies have reported inconsistent results on the association between the use of benzodiazepine and the risk of cancer. We investigated the association by using a meta‐analysis. We searched PubMed, EMBASE, and the bibliographies of relevant articles to locate additional publications in January 2016. Three evaluators independently reviewed and selected eligible studies based on predetermined selection criteria. Of 796 articles meeting our initial criteria, a total of 22 obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 56 publications
0
15
0
2
Order By: Relevance
“…Currently, there is still a lack of conclusive experimental data, but alarm signals for cancer risk have been raised by researchers for hypnotic drugs based on observational study findings [ 26 , 27 , 28 , 33 ]. A previous meta-analysis of 22 observational studies (18 case-control and 4 cohort studies) concluded there is an overall estimate of 19% increased cancer risk, with a significant dose–response trend, among benzodiazepines users over non-users [ 47 ]. A meta-analysis performed by Kim et al (2017) included 6 observational epidemiological studies (3 case-control and 3 cohort studies) [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is still a lack of conclusive experimental data, but alarm signals for cancer risk have been raised by researchers for hypnotic drugs based on observational study findings [ 26 , 27 , 28 , 33 ]. A previous meta-analysis of 22 observational studies (18 case-control and 4 cohort studies) concluded there is an overall estimate of 19% increased cancer risk, with a significant dose–response trend, among benzodiazepines users over non-users [ 47 ]. A meta-analysis performed by Kim et al (2017) included 6 observational epidemiological studies (3 case-control and 3 cohort studies) [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the lack of conclusive experimental data, alarm signals for cancer risk have been raised by researchers for benzodiazepines and the Z-drugs based on observational study findings [ 136 – 139 ]. In attempts to get a clear answer to this quandary, Kim et al published a 2016 meta-analysis of 22 observational studies (18 case–control and 4 cohort) which concluded an overall estimate of 19% increased cancer risk, with a significant dose-response trend, among benzodiazepine users over non-users [ 140 ]. There does exist a fine degree of granularity when it comes to the determination of cancer risk from benzodiazepines/Z-drugs as certain types of cancer (i.e., esophageal, brain, pancreatic) and certain agents (lorazepam, clonazepam, zopiclone) carry greater statistical weight, driving the overall association [ 137 , 140 ].…”
Section: Cancermentioning
confidence: 99%
“…In attempts to get a clear answer to this quandary, Kim et al published a 2016 meta-analysis of 22 observational studies (18 case–control and 4 cohort) which concluded an overall estimate of 19% increased cancer risk, with a significant dose-response trend, among benzodiazepine users over non-users [ 140 ]. There does exist a fine degree of granularity when it comes to the determination of cancer risk from benzodiazepines/Z-drugs as certain types of cancer (i.e., esophageal, brain, pancreatic) and certain agents (lorazepam, clonazepam, zopiclone) carry greater statistical weight, driving the overall association [ 137 , 140 ]. Given that most of the studies included in the meta-analysis are retrospective, the authors address the limitations fairly by reminding us of confounding by indication (cancer patients more likely to use anxiolytic medication) and unmeasured confounding (alcohol and smoking) [ 140 ].…”
Section: Cancermentioning
confidence: 99%
“…Patients may become dependent on BZDs to avoid withdrawal symptoms 1–3. Studies have shown several adverse consequences related to the long-term use of BZD, including fracture,4 5 cancer6 and car accidents7 in any age group.…”
Section: Introductionmentioning
confidence: 99%